Effect of Staff Migration on Kidney Transplant Activity in United Network for Organ Sharing Region 1 Transplant Centers. (September 2014) - Saidi, Reza F.; Khaksari, Sahriar; Ko, Dicken S. C.
Organ shortage is unquestionably the greatest challenge facing the field of transplantation today. Transplant centers are constantly competing with one another for limited numbers of organs for their recipients. Recruitment of specialized transplant surgical expertise and leadership is thought to enable a center to grow in volume and thus profitability in the increasingly difficult world of health care reimbursement. In this study, the pattern of kidney transplants at 13 different centers in the United Network for Organ Sharing's region 1 is examined: the comparison is between transplant volume before and after changes in the centers' leadership between 2000 and 2011. Each center's kidney transplant volume showed a significant increase after a leadership change that ultimately regressed to the center's baseline. This study is the first to show that behavioral changes in transplant center competition cause transient increases in transplant volume that quickly regress back to mean levels.